The impact of preoperative nutritional screening, ERAS protocol, and mini-invasive surgery in surgical oncology: A multi-institutional SEM analysis of patients with digestive cancer - Lorenzon, Laura; Caccialanza, Riccardo; Casalone, Valentina; Santoro, Gloria; Delrio, Paolo; Izzo, Francesco; Tonello, Marco; Mele, Maria Cristina; Pozzo, Carmelo; Pedrazzoli, Paolo; Pietrabissa, Andrea; Fenu, Piero; et al. (Frontiers in Nutrition, 2023)
Background. Mini-invasive surgery (MIS), ERAS, and preoperative nutritional screening are currently used to reduce complications and the length of hospital stay (LOS); however, inter-variable correlations have seldom been explored. This research aimed to define inter-variable correlations in a large series of patients with gastrointestinal cancer and their impact on outcomes. Methods. Consecutive cancer patients who underwent radical gastrointestinal surgery between 2019-2020 were analyzed. Age, BMI, comorbidities, ERAS, nutritional screening, and MIS were evaluated to determine their impact on 30-days complications and LOS. Inter-variable correlations were measured, and a latent variable was computed to define the patients' performance status using nutritional screening and co-morbidity. Analyses were conducted using structural equation modelling (SEM). Results. Out of the 1968 eligible patients, 1648 were analyzed. Univariable analyses documented the benefit of nutritional screening for LOS and MIS and ERAS (≥7 items) for LOS and complications; conversely, male sex and comorbidities correlated with complications, while increased age and BMI correlated with worse outcomes. SEM analysis revealed that: a) the latent variable is explained by the use of nutritional screening (p0·004); b) the variables were correlated (age-co-morbidity, ERAS-MIS, ERAS-nutritional screening, p<0·001); and c) their impact on the outcomes was based on direct effects (complications: sex, p0·001), indirect effects (LOS: MIS-ERAS-nutritional screening, p<0·001; complications: MIS-ERAS, p0·001), and regression-based effects (LOS: ERAS, MIS p<0·001, nutritional screening p0·021; complications: ERAS, MIS p<0·001, sex p0·001). Finally, LOS and complications were correlated (p<0·001). Conclusions. ERAS, MIS, and nutritional screening are beneficial in surgical oncology; however, the inter-variable correlation is reliable, underlying the importance of the multidisciplinary approach.